Efektivitas Penerapan Metode Penugasan Berbasis Portopolio Dalam Pembelajaran Gambar Teknik - Tanisha Gusach; Dedy Suryadi; Siti Nurasiyah; Irma Widianingsih (Jurnal Pendidikan Teknik Bangunan, 2021)
In accordance with the core competencies and aspects of achievement in the Engineering Drawing subject, a portfolio-based assignment method is given whose contents are a collection of student pictures. This study aims to see how the effectiveness of portfolio-based assignments on the achievements that must be obtained in the subject of Engineering Drawing. The results of this study indicate that in the student learning process the teaching materials used are less effective, the delivery of teaching materials is quite effective, portfolio-based assignments are quite effective, and task assessment is less effective. On learning outcomes, on average, students get good grades with reference to the lowest score criteria, students achieve complete learning using the KKM.